Congenital Orbital Teratoma of the Newborn: A Rare Case Report - Yuliawati, Putu; Wetarini, Krisnhaliani; Sutyawan, I Wayan Eka; Surasmiati, Ni Made Ayu; Utari, Ni Made Laksmi; Sunariasih, Ni Nyoman (Jurnal Kedokteran Brawijaya, 2024)
Congenital orbital teratoma is a rare and complex congenital anomaly due to abnormal tissue growth within the orbit. This case report aims to highlight the significance of early prenatal screening in identifying congenital orbital teratoma and its potential complications. A 6-day-old male newborn presented with macrocephaly and a unilateral massive protrusion of the left eye. Prenatal ultrasonography performed at 36 weeks gestation showed a suspicion of fetal craniofacial mass. Further brain CT scan revealed an orbital heterogeneous mass, with calcified components dominantly in the anterior and middle cranial fossa into the left orbit, which was subsequently diagnosed as congenital orbital teratoma associated with non-communicating hydrocephalus. This finding prompted an urgent ventriculoperitoneal (VP) shunt. Unfortunately, despite prompt intervention, the patient passed away after the procedure. Pathological examination was compatible with an immature teratoma. Multidisciplinary management is warranted to improve diagnostic screening and refine management strategies for better outcomes in such cases.